2001
DOI: 10.1159/000046087
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of CML-Hb in Predicting the Progression of Bone Cysts in Dialysis-Related Amyloidosis

Abstract: Background/Aim: Carboxymethyllysine is one of the common advanced glycation end products in vivo. In a previous report, we were the first to describe the increase of circulating carboxymethyllysine-hemoglobin (CML-Hb) levels in hemodialysis patients, particularly in patients with dialysis-related amyloidosis (DRA). The aim of this study was to investigate the predictive value of CML-Hb in the progression of DRA using computed tomography images of 2-year or 3-year follow-up periods of patients with amyloid bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…RAGE expressed by synovial fibroblasts may mediate some of these responses involved in DRA [158]. CML-hemoglobin has been proposed as a possible predictor of progression of bone cysts in DRA [159]. Thus, at least a close relation between AGE accumulation in renal failure and the development of dialysis related amyloidosis exists.…”
Section: Age In Renal Insufficiency Renal Replacement Therapy and Kimentioning
confidence: 99%
“…RAGE expressed by synovial fibroblasts may mediate some of these responses involved in DRA [158]. CML-hemoglobin has been proposed as a possible predictor of progression of bone cysts in DRA [159]. Thus, at least a close relation between AGE accumulation in renal failure and the development of dialysis related amyloidosis exists.…”
Section: Age In Renal Insufficiency Renal Replacement Therapy and Kimentioning
confidence: 99%
“…Major clinical signs of DRA in HD patients were: (i) polyarthralgia; (ii) CTS; (iii) bone cyst; and (iv) destructive spondylo‐arthropathy. Significant correlation between circulating CML‐Hb level and the progress of bone amyloid cyst, was quite recently reported and suggested that the formation of AGEs is closely involved in development and/or progress of bone amyloid cysts (16).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are required to show whether serum levels of AGE or CML can be used to predict severity or duration of a chronic inflammatory disease and thus predict the occurrence or progression of AA amyloidosis, as it was demonstrated for A␤2M amyloidosis. 35 Statistical analyses failed to show any correlation between serum or splenic CML levels and amounts of RAGE mRNA, indicating that transcription of RAGE does not depend on CML levels only. At least three different ligands, which occur during amyloidogenesis, compete for binding to RAGE: SAA1.1, AA fibril protein, and CML.…”
Section: Prevalence and Pathogenesis Of Ages In Amyloidosismentioning
confidence: 96%